Combined Analysis of Second- and Third-Generation Transcriptome Sequencing for Gene Characteristics and Identification of Key Splicing Variants in Wound Healing of Ganxi Goat Skin - Xue Yang; Lucheng Zheng; Junhong Huo; Wei Hu; Ben Liu; Qingcan Fan; Wenya Zheng; Qianqian Wang (Animals)
Ganxi goat is a local breed of goat unique to Jiangxi Province, China, named for its primary distribution in the Ganxi region. Ganxi goats are primarily raised through grazing, showing good adaptation to the local humid and hot climate, strong disease resistance, and occupying an important position in the local livestock industry. The skin, as the main barrier of the body, plays an indispensable role in resisting the invasion of external pathogenic factors and has received increasing attention in the medical and scientific fields. In this study, Ganxi goat skin was used as the research subject. Full-length transcriptome sequencing of Ganxi goat skin was performed using PacBio third-generation sequencing technology to supplement and improve the annotation information of the Ganxi goat genome. A combined analysis of second- and third-generation transcriptome sequencing was used to analyze the splicing variant events of hub genes (CDC20, MMP2, TIMP1, and EDN1) and the expression changes in each splicing variant in skin samples on day 0 and day 5 after surgical wounding. The regulatory role of related hub gene splicing variants in wound healing was analyzed. A total of 926,667 full-length non-chimeric sequences were obtained, optimizing the annotation information of 3794 genomic gene loci and identifying 2834 new genes, 256 new LncRNAs, 12,283 alternative splicing events, 549 genes with polyadenylation, and 112 fusion genes. Three splicing variant forms were identified in both the CDC20 and EDN1 genes, seven in MMP2, and two in TIMP1. The expression levels of most splicing variants showed significant changes in the skin samples on days 0 and 5 after wounding, potentially participating in the regulation of wound healing. This study provides fundamental data for the annotation of the goat genome and offers a reference for studying the regulatory mechanisms of wound healing.